Relationship Of Characteristics Of Pregnant Women With Tetanus Toxoid Immunization In Mangga Village - Dwi Ris Hasanah; Helena Fransysca; Nurdiana Manurung (Science Midwifery, 2021)
Pregnancy is a time when a woman carries an embryo or fetus in her body. Tetanus toxoid immunization (tetanus toxoid vaccine) is one of the efforts to prevent tetanus. Tetanus is a serious disease caused by bacteria. The report on Analysis of Trials in Indonesia in 2014 compiled by WHO (World Health Organization) in collaboration with the Ministry of Health of the Republic of Indonesia 9.8% (18,032) of 184 thousand births faced death due to low coverage of tetanus immunization.This study aims to determine the relationship between the characteristics of pregnant women and the completeness of tetanus toxoid immunization. The research methodology in this study used observational analytic with incidental sampling approach. The sample in this study were 30 pregnant women who used TT immunization. Based on the results of the chi-square test obtained p value = 0.000. This means that the p value is smaller than (0.05) thus Ho is rejected and Ha is accepted, namely the zcharacteristics of postpartum mothers with complete tetanus toxoid immunization. So from the results of this study found a gap between the results of the study and the theory that has been stated above.